iTRAQ-Based Proteomic Analysis Reveals Molecular Pathways in Potato Cold Stress Response - Huiju Yang; Mingwei Chen; Huachun Guo (Life)
Potato (Solanum tuberosum L.) is an essential crop for food and industrial production, but its cultivation in low-temperature regions is challenging. Therefore, using proteomics quantification technology based on isobaric tags for relative and absolute quantification, we investigated molecular responses in potato leaves under cold stress at 1 (L1), 3 (L3), and 6 h (L6), with normal growth as a control. A total of 3292 proteins at all stages were identified, with 125, 250, and 380 differentially abundant proteins at L1, L3, and L6, respectively. The GO and KEGG analysis revealed that these DAPs were linked to photosynthesis, oxidative phosphorylation, and the biosynthesis of ansamycins. Further association analysis showed down-regulation in aminoacyl-tRNA biosynthesis and up-regulation in pathways like alpha-linolenic acid metabolism. At L6, a significant up-regulation of cold tolerance genes was observed. This study provides insight into the proteomic mechanisms of cold tolerance in potato, laying a foundation for genetic breeding.